2020
DOI: 10.21203/rs.3.rs-41842/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlates of Children’s Physical Activity During the Covid-19 Confinement in Portugal

Abstract: Objectives: Aiming to understand the role of household variables on the percentage of physical activity (%PA) during the COVID-19 confinement, an anonymous online survey was launched to be completed by Portuguese families with children. Study Design: A Cross-sectional study design using an anonymous online survey that was launched to assess how Portuguese families with children under 13 years of age adjusted their daily routines to this situation. Methods: Separate ANOVAs were performed to investigate how fact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…When zooming in on our study population during lockdown, children who managed to adhere to PA guidelines during lockdown were significantly younger (9.2 vs. 13.2 years) and more often adhered to PA guidelines prepandemic. In line with recent findings, encouragement from parents or peers seemed important [2,4,5,32]. Moreover, in half of our population, mean time spent on PA decreased dramatically to ≤2 h/week, which was often attributed to COVID-19-related anxiety, as we ourselves as well as a recent US study reported recently [15,33].…”
Section: Discussionsupporting
confidence: 91%
“…When zooming in on our study population during lockdown, children who managed to adhere to PA guidelines during lockdown were significantly younger (9.2 vs. 13.2 years) and more often adhered to PA guidelines prepandemic. In line with recent findings, encouragement from parents or peers seemed important [2,4,5,32]. Moreover, in half of our population, mean time spent on PA decreased dramatically to ≤2 h/week, which was often attributed to COVID-19-related anxiety, as we ourselves as well as a recent US study reported recently [15,33].…”
Section: Discussionsupporting
confidence: 91%
“…Post‐onset, parents tended to attribute this rise in SMU to either the pandemic or a change in their child's learning situation (see Figure 1 and Supporting Information D theme Factors influencing screen media ). While the quantitative results did not specifically take school‐related media use into account, these qualitative findings clearly suggest parents were also seeing an inherent increase in screen time due to distance learning, as seen in other studies (Lau & Lee, 2021; Pombo et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Our first aim was to describe how children were using screen media differently pre‐pandemic versus post‐onset and parent perceptions of their child's media use. This was a confirmatory aim based on international observations of changing screen media habits in children and adolescents (Dutta et al, 2020; Eyimaya & Irmark, 2021; Lau & Lee, 2021; Pombo et al, 2020). We hypothesized that, in our qualitative data, parents would express more concern about their child's media use post‐onset and there would be a shift in how they were talking about their child's media use.…”
Section: Screen Media Use: Risks and Buffersmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, studies have revealed a weekly decrease of 2.3 hours in children’s PA in recent years, and during the lockdown, time spent in PA was decreased to 1.29 hours per week (Pietrobelli et al, 2020). During the first lockdown period in March-April 2020, Portuguese children under the age of 12 were reported to have spent 80% of their time confined to sedentary activity (Pombo et al, 2020), with most of that time in front of a computer screen, due to online classes.…”
Section: Introductionmentioning
confidence: 99%